Practical aspects and prospects for formation of financial and industrial groups in Uzbekistan - J. X. Ataniyazov; S. S. Shirinova (Финансы: теория и практика)
This article examines the conditions for the formation of financial and industrial groups in Uzbekistan and the participation of commercial banks in their activities. The purpose of the study is to formulate recommendations for creating the necessary conditions for the formation and organization of the activities of financial and industrial groups. The authors used the following research methods: grouping, abstraction, comparative analysis, structural analysis, and scientific forecasting. This article also describes the role of financial and industrial groups in the development of the economy and assesses the possibility of creating financial and industrial groups with the participation of commercial banks. In addition, the features and prospects for the creation of financial and industrial groups in Uzbekistan have been identified. The authors conclude that there are the following grounds for the formation of financial and industrial groups with the participation of commercial banks in Uzbekistan: the volume of commercial bank loans allocated to the real sector of the economy is increasing, there is a great need for financial resources to modernize production, as well as technical and technological re-equipment of enterprises. The formation of financial and industrial groups in the national economy will lead to the sustainable development of the industrial sector, ensuring the stability of the financial and banking system and increasing the competitiveness of the national economy.